Temperaturas internas y frecuencias de muda en crías de Tupinambis teguixin (Reptilia: teiidae) bajo condiciones controladas - Yanosky, Ángel Alberto (1991)
Internal or cloacal temperatures (CT) in tegu offspring were studied in an environmental chamber and the were higher than ground temperatures (GT) when these were low, except for a GT of 26.5ºC for which CT was similar. The increase in GTs means an increase in CTs up to 37.21ºC for which the difference between CT and GT were the greatest. The increase of GT above 31.5ºC was related with a decrease in CT: Inmatures CT behaved in a similar way. At 40ºC in GT, animals could not regulate their CT and died. Data depicted here show a certain degree of endotermy. Moulting was more frequent in older juveniles than in younger with a greater range of values for the last ones. Tegu moults were incomplete and they feed though moulting.